Enhanching Speaking Ability on Students Of University Of Asahan Through Flash Cards - Hasibuan, Derliana; Sambayu, Harry; Meidipa, Lisa Fitri (Yayasan Kajian Riset dan Pengembangan RADISI, 2024)
The research's objectives are to determine whether and to what extent flashcards can improve speaking abilities in University of Asahan information technology students and to describe the classroom environment when flash cards are used in speaking classes. Class action research is the research methodology used. The researcher employed questionnaires, observations, interviews, document analyses, and tests to gather the data. Prior to doing research (pre-test) and following the use of flash cards (post-tests 1 and 2), the researcher administered the tests. To determine the improvements in speaking skills among the students, the mean results from each exam were compared. The improvements in the pre-test mean score of 49, the cycle 1 post-test mean score of 75, and the cycle 2 post-test mean score of 79 show the advancements. In addition, the class environment was improved because: 1) students participated actively; 2) speaking class participation was equal; 3) students were encouraged to speak English much more than Indonesian; and 4) student interaction was greatly improved